1996
DOI: 10.1007/bf01807038
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian status influences the skeletal effects of tamoxifen in adult rats

Abstract: Tamoxifen (TAM), an antiestrogen used in adjuvant therapy for breast cancer, is currently being evaluated for prevention of breast cancer in premenopausal and postmenopausal disease-free women. In light of this clinical application in young women, the skeleton's potential predisposition for osteoporosis following long-term treatment with an antiestrogen is a concern. In postmenopausal women being treated for breast cancer TAM was shown to prevent bone loss. There is little information, however, about the skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Dietary nitrate concentrations of ∼0.1 mmol/kg/d in rats have been demonstrated to lower blood pressure 16, and intakes of ∼372 mg total nitrate per day reverse vascular dysfunction in older adult humans 42. Three weeks of dietary nitrate supplementation, a period adequate to observe rapid OVX‐associated bone loss and treatment‐associated effects 43, had no effect on tibial cancellous or cortical bone mass and architecture or histomorphometric indices of bone formation or resorption in OVX rats. Furthermore, increased dietary nitrate had no significant effect on serum biochemical markers of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary nitrate concentrations of ∼0.1 mmol/kg/d in rats have been demonstrated to lower blood pressure 16, and intakes of ∼372 mg total nitrate per day reverse vascular dysfunction in older adult humans 42. Three weeks of dietary nitrate supplementation, a period adequate to observe rapid OVX‐associated bone loss and treatment‐associated effects 43, had no effect on tibial cancellous or cortical bone mass and architecture or histomorphometric indices of bone formation or resorption in OVX rats. Furthermore, increased dietary nitrate had no significant effect on serum biochemical markers of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…1991). These and more recent studies (Frolik et al 1996;Li et al 1996;Sibonga et al 1996;Ke et al 1997) have shown that tamoxifen prevents ovariectomy-induced bone loss. In intact female rats the results are somewhat conflicting, some studies show no effect (Jordan et al 1987;Moon et al 1991) whereas others show a slight tamoxifen-related decrease of bone tissue (Feldmann et al 1989;Hard et al 1993;Sibonga et al 1996).…”
mentioning
confidence: 87%
“…These and more recent studies (Frolik et al 1996;Li et al 1996;Sibonga et al 1996;Ke et al 1997) have shown that tamoxifen prevents ovariectomy-induced bone loss. In intact female rats the results are somewhat conflicting, some studies show no effect (Jordan et al 1987;Moon et al 1991) whereas others show a slight tamoxifen-related decrease of bone tissue (Feldmann et al 1989;Hard et al 1993;Sibonga et al 1996). In postmenopausal women, tamoxifen has been shown to lack negative effects on bone metabolism (Nakanishi et al 1995;Barni et al 1996;Kalef-Ezra et al 1996;Powles et al 1996) and some studies even indicate a weak antiosteoporotic effect (Nakanishi et al 1995;Barni et al 1996).…”
mentioning
confidence: 87%
“…These observations suggest similar skeletal mechanisms of action of estrogen in rats and humans. Furthermore, the skeletal changes in rats in response to partial estrogen agonists have accurately predicted the differential responses of pre-and postmenopausal women to tamoxifen treatment (10,11).…”
mentioning
confidence: 99%